2016
DOI: 10.1063/1.4967919
|View full text |Cite
|
Sign up to set email alerts
|

A study on Si/Al2O3 paramagnetic point defects

Abstract: In this contribution, negative charges and electronic traps related to the Si=Al 2 O 3 interface were measured and related to paramagnetic point defects and molecular vibrations. To this end, contactless capacitance voltage measurements, X-band electron paramagnetic resonance (EPR), and infrared spectroscopy were carried out, and their results were compared. A change in the negative charge density and electron trap density at the Si=Al 2 O 3 interface was achieved by adding a thermally grown SiO 2 layer with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Introducing significant band bending at the silicon side of the Si/a-Al 2 O 3 interface leads to reduction of the surface recombination, thus improving the solar cell efficiency. Formation of negative charges in alumina is seen as a result of electron transfer from silicon to the oxide traps thought to be either oxygen interstitials [170] or aluminum vacancies [18]. However, these trapping site models can hardly explain the thermally-activated increase of the negative charge observed when annealing a-Al 2 O 3 layers on Si at temperatures below 500 °C [171] which are insufficient for alumina crystallization.…”
Section: Effect Of Charge Trapping On Functionality Of Oxide Filmsmentioning
confidence: 99%
“…Introducing significant band bending at the silicon side of the Si/a-Al 2 O 3 interface leads to reduction of the surface recombination, thus improving the solar cell efficiency. Formation of negative charges in alumina is seen as a result of electron transfer from silicon to the oxide traps thought to be either oxygen interstitials [170] or aluminum vacancies [18]. However, these trapping site models can hardly explain the thermally-activated increase of the negative charge observed when annealing a-Al 2 O 3 layers on Si at temperatures below 500 °C [171] which are insufficient for alumina crystallization.…”
Section: Effect Of Charge Trapping On Functionality Of Oxide Filmsmentioning
confidence: 99%
“…The major challenge for atomic identification of electron trapping sites in a-Al 2 O 3 concerns the absence of electron spin resonance (ESR) signals associated with these electron states. Despite several attempts to observe electrons trapped in a-Al 2 O 3 using ESR, only signals stemming from its interface with the silicon substrate (silicon dangling bonds at the surface of the Si crystal or in the near-interface Si oxide layer) or with contaminants, mostly carbon-related, have been detected so far 7,10,[15][16][17][18][19] . We note that crystallization of alumina as a result of high temperature annealing does not eliminate electron trapping sites, suggesting that they are not caused by disorder as in a-HfO 2 The EPDS measurements were confirmed by gate side trap spectroscopy when injecting electrons from silicon and sensing' (GS-TSCIS) measurements which show a peak defect density of 1.6 × 10 19 /cm 3 at approximately 3.4 eV below the Al 2 O 3 CBM, with a significant distribution of traps from 3.0 eV below the CBM 4 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the formation of negative charges in alumina is result of electron transfer from silicon to energetically deep electron traps inside the oxide. A broad variety of models for the electron traps have been introduced, ranging from oxygen interstitials [10] to oxygen vacancies [11] and aluminum vacancies [7]. Testing the validity of these models requires understanding of how these trapping site models can explain the thermally-activated increase of the negative charge observed when annealing a-Al 2 O 3 layers on Si at temperatures below 500 °C [12].…”
Section: Introductionmentioning
confidence: 99%